Assessing Archival User Satisfaction at University Archives: a Case Study at Universitas Gadjah Mada - Setyawan, Herman; Santi, Zuli Erma (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2023)
In academic settings, it is important to understand user satisfaction on university archives to improve the quality of the archival system. This study aims to measure user satisfaction at the University Archives of Universitas Gadjah Mada. This study used a quantitative descriptive research design. The sample of this study was 38 archive users from 2023. Data on user satisfaction was collected using surveys. The result showed that the archive's quality of information, system, service, and reading room were above 91%. This study examines highly satisfied users of university archive services, identifying key factors that promote satisfaction and informing future service development. The results of this study are expected to provide practical guidance for university archive managers in improving their archive services to achieve higher levels of user satisfaction.